FINANCE AND TAX POLICY: DESIGN, IMPLEMENTATION, AND EFFECTS ON REVENUE MOBILIZATION AND GROWTH - Egamova , Nargiza (Scientific practical conference, 2025)
This article examines the role of finance and tax policy in mobilizing domestic revenue, supporting public expenditure, and promoting equitable economic growth. It synthesizes recent international evidence on tax policy reforms, tax administration improvements, and policy trade-offs faced by both developed and developing economies. The paper uses a structured literature review of IMF, World Bank and OECD reports and selected academic studies to identify effective instruments, institutional reforms, and policy sequencing. Key findings highlight (1) the central importance of broad-based taxes and removal of inefficient exemptions for revenue mobilization, (2) the complementary role of stronger tax administration and digitalization to raise compliance, and (3) the need to balance revenue goals with growth and equity through carefully designed incentive structures. The article concludes with actionable recommendations for policymakers and a research agenda for future work.